SARS-CoV and other emerging coronaviruses - Baric, Ralph (Henry Stewart Talks, 2018)
Nidovirales family, Coronavirus phylogeny, Timeline of emerging coronaviruses, Virus particles and entrance, Coronavirus structure, MERS-CoV group 2c betacoronavirus, Mechanisms of CoV emergence, Role of cell surface receptors, Public health preparedness, Is SARS extinct?, Pre-pandemic group 2b SARS-like bat coronaviruses, How to test pre-pandemic potential, Virus gene organization and replication cycle, How do coronaviruses cause disease, SARS coronavirus ORF1 processing, ORF1B replicase function, SARS genome replication, SARS sub-genomic transcription, Current antiviral therapies